Enterococcus faecalis Modulates Immune Activation and Slows Healing During Wound Infection - Chong, Kelvin Kian Long (2018)
Enterococcus faecalis is one of the most frequently isolated bacterial species in wounds yet little is known about its pathogenic mechanisms in this setting. Here, we used a mouse wound excisional model to characterize the infection dynamics of E faecalis and show that infected wounds result in 2 different states depending on the initial inoculum. Low-dose inocula were associated with short-term, low-titer colonization whereas high-dose inocula were associated with acute bacterial replication and long-term persistence. High-dose infection and persistence were also associated with immune cell infiltration, despite suppression of some inflammatory cytokines and delayed wound healing. During high-dose infection, the multiple peptide resistance factor, which is involved in resisting immune clearance, contributes to E faecalis fitness. These results comprehensively describe a mouse model for investigating E faecalis wound infection determinants, and suggest that both immune modulation and resistance contribute to persistent, nonhealing wounds.